An ecological study of the free-roaming cat population in the Universiti Putra Malaysia (UPM) campus - Ibrahim Bajunid, Aina Fazlin; N. B., Salim; Cheng, N. A. B. Y.; Hassan, L. (Universiti Putra Malaysia Press, 2004)
This pilot study seeks to develop a system for the establishment of an animal population database and the identification of some of the ecological niches that sustain their existence. The study site was the built up area of the Universiti Putra Malaysia (UPM) Campus and the study was carried out during the 1st semester six-week break. Methods used for the various parts of the study were the Schnabel’s Photographic Multiple Recapture Method (photographic trapping technique) and field observations. The population of the free-roaming cats in UPM was calculated to be 533 cats with a population density of 80 cats/km2. Characteristics of the population such as their sex, age group, body condition score and health status were determined. The ecological niches researched on include the cats’ food, water and shelter procurement. It was concluded that the Schnabel’s Photographic Multiple Recapture Method had good potential to be used to develop a population database and that the issue of free-roaming cats needs more consideration and attention by the authorities.